Impact of Pharmacogenetics on High-Dose Methotrexate Toxicity in Pediatric Oncology - Luciana Maria Marangoni-Iglecias; Almudena Sánchez-Martin; Laura Elena Pineda-Lancheros; Yasmín Cura; Noelia Marquez-Pete; José María Gálvez-Navas; Nerea Báez-Gutiérrez; Adrián Manuel de La Jara-Vera; Emilia Urrutia-Maldonado; Cristina Pérez-Ramírez; Alberto Jiménez-Morales (Pharmaceutics)
Background: Childhood cancers represent a heterogeneous group of malignancies and remain one of the leading causes of mortality among children under 14 years of age, ranking second only to accidental injuries, and fourth among individuals aged 15 to 19 years. Despite notable improvements in cure rates, a substantial proportion of patients experience acute or long-term toxicities associated with treatment. Methotrexate (MTX), a chemotherapeutic agent, has been employed effectively for over six decades in the management of pediatric malignancies. High-dose methotrexate constitutes a cornerstone of pediatric cancer therapy; however, its clinical utility is frequently constrained by dose-limiting toxicities. Objectives: This study investigates the impact of genetic polymorphisms in genes involved in nucleotide metabolism, as well as methotrexate and folate metabolic pathways, on treatment-related toxicity in childhood cancer. Methods: Using real-time polymerase chain reaction, 14 polymorphisms across 12 genes were analyzed in a cohort of 107 patients. Toxicity was assessed according to the Common Terminology Criteria for Adverse Events v. 5.0. Results: Multivariate logistic regression analysis revealed that the male sex (p = 0.3) and the AA genotype of MTHFD1 rs2236225 were associated with grade III–IV gastrointestinal toxicity (p = 0.03), while the A allele of MTHFR rs1801133 and the AA genotype of GSTP1 rs1695 were associated with grade I–IV hematologic toxicity (p < 0.01 and p = 0.02, respectively). Conclusions: High-dose methotrexate (HDMTX) is a critical agent in the treatment of childhood cancers. Our findings suggest that genetic polymorphisms within methotrexate and folate metabolic pathways may serve as potential predictive biomarkers of treatment-related toxicity.